Effect of group treatment on physical inactivity among Syrian refugees. Randomized controlled trial. (30th September 2020) - Hasha, W; Fadnes, L T; Igland, J; Strømme, E M; Younes, J H; Kumar, B; Diaz, E
Abstract: Background: Refugees in Norway show low levels of physical activity, and have relatively high prevalence of pain disorders and post-traumatic symptoms. Physical inactivity can be both a cause of and a consequence of physical and mental symptoms. In CHART study (Changing Health and health care needs Along the Syrian Refugees' Trajectories to Norway), two group interventions, one based on physiotherapy and body awareness (PAAI) and the other on Teaching Recovery Techniques (TRT), were developed to treat patients with pain disorders and/or post-traumatic symptoms. Objective: As a secondary outcome of study, we assessed the effect of these group interventions on physical inactivity. Methods: We conducted a randomized controlled trial testing two group interventions. Syrian adults ≥16 years with pain and/or post-traumatic symptoms were randomized to either intervention group or control group. Effect of the intervention was measured after 8 (PAAI) and 6 (TRT) weeks, as relative risk (RR) with 95% confidence intervals for being inactive for intervention versus control groups, using log-binomial regression with adjustment for baseline inactivity and type of intervention (PAAI or TRT). Results: 177 Syrian refugees were recruited between July 2018-September 2019. 88 were randomized to the intervention group and 89 to the control group. Mean age was 35 years (SD 11) and 38% were women. Inactivity at recruitment was reported by 126 (71%) participants. The follow-up questionnaire was completed at 6/8 weeks by 116 (66%) participants. At that point, 39% in the intervention group were inactive as compared to 56% in the control group. RR for inactivity for the intervention group adjusted for inactivity at baseline was 0.68 (0.47-0.99) and remained 0.68 (0.48-0.99) when further adjusting for type of intervention (PAAI vs TRT). Conclusions: PAAI and TRT group interventions reduced inactivity among refugees by 32%. Effect on physical inactivity was similar between PAAI and TRT interventions. Key messages: Public health care should be aware of physical inactivity, especially in relation to pain disorders and post-traumatic symptoms among refugees. Group treatment interventions succeeded to encourage refugees to increase their physical activity.